The Forgiveness Classroom: Bringing Together Students from Both Sides of the Walls through Deep Listening - Ruth Henderson (Journal of the Assembly for Expanded Perspectives on Learning, 2010)
This essay describes a forgiveness course taught in prisons and on college campuses. The course served as a bridge for Endicott College students and inmates from the Maine Correctional Center at Windham, highlighting how deep listening may reduce violence and promote understanding.